Efficacy of Calcium Phosphate Composite Bone Graft in Treatment of Periodontal Intrabony Defects: Clinico-radiographic Study - Bhatnagar, Shruti; Debnath, Surangama; Siddeshappa, Sriniwasa Tenkasale; Yeltiwar, Ramreddy K; Dewan, Vikas (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Introduction: Regeneration of periodontium is always difficult to achieve regardless of all advancement. In an attempt to refine, various materials have been tried and tested. The present study was carried out to evaluate regenerative potential of easy-graft CRYSTAL in intrabony defects, clinically, and radiographically. Methods: This randomised split-mouth study was conducted at Rungta College of Dental Sciences and Research from 2015 October to 2015 October. Intrabony pockets more than 5 mm and radiographic evidence of vertical bone loss were selected from 15 patients having two sites each. The chosen sites were randomly divided into test sites: open flap debridement (OFD) with easy-graft CRYSTAL and control sites (OFD). The clinical parameters evaluated were Plaque Index, Gingival Index, Probing Pocket Depth, Relative Attachment Level, and Gingival Recession at baseline, three months, and six months postoperatively. Radiographic parameters recorded were Defect Fill and Percentage of Defect Fill at baseline, three months, and six months. Data were analysed in SPSS v.20. Results: At six months, improved clinical and radiographic values were obtained compared to baseline. The plaque and gingival index showed statistically significant reduction. Both groups showed statistically significant reduction in mean probing pocket depth and gain in relative attachment level. Mean gingival recession score was increased in both the group but was not significant. There was significant increase in Defect Fill and Percentage of Defect fill in both groups with better bone fill in test group. Conclusion: Easy-graft CRYSTAL is a potential regenerative material for the treatment of periodontal intrabony defects.